Roles of technology in improving perishable food supply chains - Mona Haji; Laoucine Kerbache; Mahaboob Muhammad; Tareq Al-Ansari (Logistics, 2020)
Food supply chains are considered to be more complex systems than other types of supply chains. This complexity is due to the continuous changes taking place, particularly in ensuring the quality of food products throughout the entire supply chain, from growing, procurement of resources, production, and management of stock, to distribution to the final consumers. For that, food supply chain markets have become more highly developed in the use of modern technologies, and have begun to implement them in their logistical systems to satisfy their customers' needs. The main objectives of this review are to identify the different technological implementations in different phases of the food supply chain processes and point out the key factors for using technologies to improve the characteristics of the perishable food supply chain. A total number of 137 articles were analyzed in this research to achieve these review objectives. Some of the various technologies found in different phases of the food supply chain were radio frequency identification (RFID), the Internet of Things (IoT), blockchain, three-dimensional printing (3DP), autonomous vehicles, and unmanned aerial vehicles (UAVs). These technologies were found in different phases of the food supply chain and improved the efficiency of supplying perishable foods. The review identified different characteristics of the perishable food supply chain. The main finding indicated that technological implementation enhances the efficiency and sustainability of the food supply chains and helps to retain perishable food characteristics.
Keywords: 650; food supply chain; traceability technologies; perishable foods; supply chain innovation